Pengaruh Interval Training Terhadap Peningkatan VO₂MAX Pada Pemain Tim Sepak Bola Mahasiswa STKIP-PGRI Pontianak - Hardika, Nevi (IKIP PGRI Pontianak, 2013)
Football is also the sport most favored by students and college students, this can be seen with the extracurricular school football, SME (Student Activity Unit). In Penjaskes study program STKIP-PGRI Pontianak itself has had a football team that deliberately prepared to face the competitions between the University, the College and other competitions.Interval Training is a series of events physical exercise that is repeated is interrupted by periods of recovery. Interval Training is an exercis program that consist of a repetition period of work punctuated by periods of rest. Light exercise is usually caried out at this rest period. In practice this interval there are three things must be considered as a guideline during exercise (treatment) regular intensity, duration, and frequency. Oxygen maxsimal Volume (VO₂max) This is a level of ability of the body expressed in liters per minute or milliliter / min / kg body weight. Please also the physiology of the human body every cell needs oxygen to convert food energy to ATP (adenosine triphosphate) which is ready to work every cell that is at least consume oxygen in the muscle is at rest. Contracting muscle cells requires a lot of ATP. As a result, the muscles used in exercise requires more oxygen to muscle cells and produce CO₂. Fast or slow fatigue by an athlete can be estimated from the aerobic capacity of athletes that are less good. Aerobic capacity indicates the maximum capacity of oxygen used by the body (VO₂max), the more oxygen is absorbed by the body showed the better performance of the muscles in the works so that substances which cause the remnants of exhaustion amount will be less. Therefore, for these achievements can not be separated from Interval Training as an integral part of the formation of resistance respirasinya therefore also need to be developed so that the energy system durability energy system can be achieved as expected. The higher the VO₂max, an athlete in question will also have endurance and stamina special.Keywords: Interval Training, VO₂max.